Applying The Personal Knowledge Management In Network Quality And Value Creation Toward Sustainable Competitive Advantage (Sebuah Konseptual Model Pada Industri Garmen Di Salatiga) - Windi Novia Ratri Wardhani; Ratih Pratiwi; Sunarto Sunarto; Riesmita Kustanti; Nanang Yusroni (International Journal of Management, Business, and Social Sciences, 2022)
Abstract Organizations must manage information and knowledge effectively and allow knowledge-based value creation. This study examines the role of personal knowledge management in increasing Value creation to achieve sustainable competitive advantage. This research is explanatory research using quantitative descriptive-analytical methods. Respondents are managers of 30 garment companies in Salatiga, the sampling method used is a census and scoring using a Likert scale of 1 to 5, and the data is processed using SEM AMOS software. The results showed that personal knowledge management had a positive and significant effect on value creation. Personal knowledge management has a positive and significant effect on sustainable competitive advantage. Value creation was found to positively and significantly affect sustainable competitive advantage. Network quality strengthens the influence of personal knowledge management and network quality on sustainable competitive advantage. Further research is suggested to examine the influence of other factors that influence value condition to knowledge management by considering the quality factor of HR Industry players and product marketers who can competitiveness/ innovativeness in achieving sustainable competitive advantage Keyword: Sustainable competitive advantage, personal knowledge management, value creation, network quality